Strategi Pembentukan Karakter Toleransi pada Siswa Sekolah Dasar Multikultur dan Dwibahasa SD Pribadi di Kota Bandung - Asep Muhaemin Al-Ansori (Universitas Padjadjaran, 2018)
The education of tolerance character strives for good ethics, mutual respect, and respect between students and teachers at school. This study describes the strategy, character of tolerance carried out by a multicultural and bilingual school in the city of Bandung. The method used in this research is a qualitative method with a case study approach. The data was collected by using interview and participant observation technique. The results show that the school implemented two strategies in building the character of tolerance in students, those are learning activities in the classroom and outside the classroom. Learning activities in the classroom are packaged in Rehbelik subjects, English, and thematic subjects. The activities outside the classroom are packaged in the form of performances, morning line, charity day events, and field trips. Both of these strategies describe a process of socialization and enculturation of the tolerance character in the cultural background of formal education.